2000
DOI: 10.1007/s004170050016
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal ERG in chloroquine retinopathy: regional variance of retinal dysfunction

Abstract: Chloroquine retinopathy of different severity presents with characteristic alterations in the multifocal electroretinogram. Regional distribution of cone dysfunction is in agreement with previously reported histologic findings. The multifocal electroretinogram can detect retinal dysfunction in chloroquine retinopathy even when the full-field electroretinogram is normal and retinal alterations are subtle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 10 publications
4
39
1
2
Order By: Relevance
“…Recent studies have reported cases that, like our patient, had significant mfERG abnormalities despite being asymptomatic with normal or minimal clinical findings. [16][17][18] Typically, the mfERG will demonstrate a paracentral ring depression of signals around the fovea as was seen in our patient. 19 Moschos et al 19 reported that early cessation of hydroxychloroquine in patients resulted in improvement of mfERG patterns and reversible of toxicity over a period of 6 months.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies have reported cases that, like our patient, had significant mfERG abnormalities despite being asymptomatic with normal or minimal clinical findings. [16][17][18] Typically, the mfERG will demonstrate a paracentral ring depression of signals around the fovea as was seen in our patient. 19 Moschos et al 19 reported that early cessation of hydroxychloroquine in patients resulted in improvement of mfERG patterns and reversible of toxicity over a period of 6 months.…”
Section: Discussionsupporting
confidence: 58%
“…31 The recording protocols have been described in detail elsewhere. 32,33 The EOG was recorded with a ramp test method. 34 Full-field ERG recordings were done with maximal dilated pupils using a Nicolet Spirit and Ganzfeld (Nicolet, Madison, Wisconsin, USA).…”
Section: Methodsmentioning
confidence: 99%
“…mfERG has been used in the assessment of chloroquine and hydroxychloroquine retinal toxicity. 130,162,190,192,204,234,285,303 The most characteristic mfERG findings specific to chloroquine and hydroxychloroquine retinal toxicity is the parafoveal reduction in P1 response amplitude and delays in N1 and P1 implicit times 130,192,303 (Fig. 7).…”
Section: Toxicity Due To Systemic Agents Chloroquine and Hydroxychlormentioning
confidence: 99%